FIELD EXPERIENCE IN THE COURSE OF EPIDEMIOLOGY APPLIED TO SUS SERVICES – EPISUS FUNDAMENTAL:: EXPERIENCE REPORT (Citizenship in Action: Extension and Culture Magazine, 2023)
The present article aimed to report the description experience’s of the steps from the monitoring cicle in the perception field background of the Training Program in Applied Epidemiology for SUS services. It is a descriptive study, using a form for interview the participants of the health family team located in the Boca do Rio sanitary district, in Salvador – Bahia, during the time of August to October 2018. Were identified strenghts and intrisic points in the unit of health family, as well as threats and oportunities which depends on others health administrative instances or instituitons from differents sectors for the monitoring cicle performance. Also were stratified possible causes for the deficiency/absence of diarrhoeal acute diseases monitoring and finally, were classified the circunstances in accordance with the control grade of the team health familymembers and was held a feedback work for the team in order to promote a reflection about themonitoring cicle steps and show  recommendations for improviment in the quality of it. It concludes that despite of the health units in primary care are a privileged space for development of monitoring actions, it is noticed in this work field that the systematization of epidemiological data that should be interpreted and updated routinely by the health team, are still actions performed by technicians from other instances, either by professionals from the epidemiological surveillance of the sanitary district or the Surveillance Directorate to Health Department of the Municipal Health Department of Salvador. The relevance of the EPI-SUS field activity, as an extension activity, is also highlighted for the development of a critical reflection on the reality by the trainees.
Keywords: Epidemiology. Epidemiological monitoring. Permanent Education. Health services..